Health-Improving Potential of Dancing Exercises in Physical Education of Students of Higher Educational Institutions - Т. М. Кравчук; О. С. Роганіна (OVS LLC, 2015)
Research objective: to determine the health-improving potential of dancing exercises used in physical education of female students of higher educational institutions.  Research methods: study and analysis of pedagogical, scientific and methodological literature on the subject matter of the research; observations, questionnaires, functional tests; statistical methods of data reduction. Conclusions. As part of the study, the use of dancing exercises in the physical education of female students of higher educational institutions proved contributing to a significant increase in the level of their physical health in general and improvement of some of its indicators, including strength and life indices, heart rate recovery time after 20 squats. Dancing exercises also boost spirits, improve health and activity of the female students, which the study proved statistically.